Business Development Training And Assistance For SMEs: Pelatihan dan Pendampingan Pengembangan Usaha Pada UKM - Fitriyah, Hadiah; Setiyono, Wisnu Panggah; Hanun, Nur Ravita (Procedia of Social Sciences and Humanities, 2022)
UKM "Blimbing Wangi" continues to innovate by developing a new business, namely Kedai WMP. The WMP shop provides a variety of culinary specialties from the Watesari village with star fruit as a culinary icon, the marketing of this business is still limited to meeting the needs of local residents and local tourists and this business is still managed with simple business management governance, even though it can be developed in a professional manner for development and performance. business can be sustainable. Seeing conditions like this, it needs to be developed through training and business development assistance. The training and business assistance implemented are business management and simple bookkeeping training to improve business performance